Off loading wheelchair cushion provides best case reduction in tissue deformation as indicated by MRI. Issue 3 (August 2017) - Call, Evan; Hetzel, Thomas; McLean, Chad; Burton, Joshua N.; Oberg, Craig
Abstract: Off-loading or the Orthotic approach to wheelchair seating has been used successfully to provide seating that optimizes tissue protection at the ischial tuberosities (ITs), sacrum and greater trochanters. Recent publications indicate the significance of preventing tissue compression to reduce ulcer formation. Comparative Magnetic Resonance Imaging (MRI) of individuals seated on two cushion types provides direct evidence of tissue unloading resulting in the reduction in tissue compression. Measurement of tissue compression in MRI images provides the cumulative impact of compression and shear resulting in ultimate tissue thickness documented here. In this study's application of MRI to off-loading cushions (OLC), an alternate form of tissue protection was observed. Instead of incorporating immersion and envelopment, loads were transferred from high-risk areas, such as bony prominences, to lower risk soft tissues. This method shows both shearing and compression of load bearing tissues in seated individuals with the OLC in place. Tissue thickness measurements determined by MRI analysis indicate that the OLC provides greater reduction in tissue deformation than the air cell cushion (ACC). Deformation of tissues loaded by the OLC is not significantly different from the deformations seen with the ACC. This research represents the first reported use of MRI to document the comparative off-loading capabilities of two cushions and the resultant tissue compression and ulceration risk. While MRI analysis may not be incorporated in daily cushion prescription, this paper proposes a methodology in which MRI analysis of tissue deformation on comparative cushions allows the determination of best-case cushion selection for reduction of ischial pressure ulcer (PU) risk. Highlights: First use of MRI for tissue distortion and compression with wheelchair cushions. Comparison of tissue distortion on offloading cushions versus air cell cushions. OLC reduce compression at ITs, no increase in compression inferior to acetabulum. Establishes method to better understand the effect of WC cushions on pelvic region.